2018
DOI: 10.1001/jamasurg.2017.3142
|View full text |Cite
|
Sign up to set email alerts
|

Humanitarian Surgical Care in the US Military Treatment Facilities in Afghanistan From 2002 to 2013

Abstract: Medical units of the US military have operated for more than 15 years in Afghanistan, a country with among the lowest estimates of access to safe, timely surgical and anesthesia care. 1 Surgeons from the US military have delivered humanitarian surgical care (HSC) to local national civilians throughout the conflict, although previous large reports about this care focused on children. 2,3 To provide a more comprehensive accounting, we conducted a retrospective study on HSC provided by deployed US military medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Emergencies required significantly more postoperative care and resulted in higher reoperation rates. In 2017, Weeks et al ,18 through a large retrospective series with more than 10 000 patients, reported significantly longer LOS, more procedures and more blood transfusions for patients operated for war-related procedures. The mortality rate was higher for these cases but was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Emergencies required significantly more postoperative care and resulted in higher reoperation rates. In 2017, Weeks et al ,18 through a large retrospective series with more than 10 000 patients, reported significantly longer LOS, more procedures and more blood transfusions for patients operated for war-related procedures. The mortality rate was higher for these cases but was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Cultural competency has gained increasing recognition not only as an essential component of effective global health engagement but also as a key to improving health care disparities domestically . Considering the number of factors that can increase the cultural distance between the deployed military surgeon and local populations and the volume of contact we demonstrated, focused training seems a reasonable prerequisite to deployment, although how best to integrate such training amidst mission-essential requirements will remain a challenge. For an organization that has already prioritized cultural competency in special operations forces training, this is certainly an achievable task if it is valued appropriately.…”
mentioning
confidence: 95%
“…Previous publications have addressed certain aspects of the US military’s provision of humanitarian surgical care to specific patient populations such as burns, orthopedic injuries, and children 1–6,9–14. No comprehensive descriptive analysis of the overall epidemiologic and workload of humanitarian care performed in US combat zones has been conducted.…”
mentioning
confidence: 99%
“…Previous publications have addressed certain aspects of the US military's provision of humanitarian surgical care to specific patient populations such as burns, orthopedic injuries, and children. [1][2][3][4][5][6][9][10][11][12][13][14] No comprehensive descriptive analysis of the overall epidemiologic and workload of humanitarian care performed in US combat zones has been conducted. Understanding the injury patterns and resources required to support humanitarian missions are important considerations for the military given that surgical teams are not staffed or equipped to provide care to the civilian population.…”
mentioning
confidence: 99%